Incidence of chronic kidney disease among people with diabetes: A systematic review of observational studies - Koye, D.; Shaw, J.; Reid, Christopher; Atkins, R.; Reutens, A.; Magliano, D. (Wiley-Blackwell Publishing Ltd., 2017)
Aims: The aim was to systematically review published articles that reported the incidence of chronic kidney disease among people with diabetes. Methods: A systematic literature search was performed using MEDLINE, Embase and CINAHL databases. The titles and abstracts of all publications identified by the search were reviewed and 10 047 studies were retrieved. Results: A total of 71 studies from 30 different countries with sample sizes ranging from 505 to 211 132 met the inclusion criteria. The annual incidence of microalbuminuria and albuminuria ranged from 1.3% to 3.8% for Type 1 diabetes. For Type 2 diabetes and studies combining both diabetes types, the range was from 3.8% to 12.7%, with four of six studies reporting annual rates between 7.4% and 8.6%. In studies reporting the incidence of eGFR < 60 ml/min/1.73 m2 using the Modification of Diet on Renal Disease (MDRD) equation, apart from one study which reported an annual incidence of 8.9%, the annual incidence ranged from 1.9% to 4.3%. The annual incidence of end-stage renal disease ranged from 0.04% to 1.8%. Conclusions: The annual incidence of microalbuminuria and albuminuria is ~ 2-3% in Type 1 diabetes, and ~ 8% in Type 2 diabetes or mixed diabetes type. The incidence of developing eGFR < 60 ml/min/1.73 m2 is ~ 2-4% per year. Despite the wide variation in methods and study design, within a particular category of kidney disease, there was only modest variation in incidence rates. These findings may be useful in clinical settings to help understand the risk of developing kidney disease among those with diabetes.